An explorative study of the training needs of investigating officers interviewing young victims of sexual abuse - Coetzee, Colette (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEdPsych (Educational Psychology))--University of Stellenbosch, 2005.